The الكشف عن أنماط الفيروسات الغدية الطيرية المعزولة من حالات التهاب الكبد ذي المشتملات عند دجاج اللحم في سورية: الفيروسات الغدية الطيرية المنتشرة في سورية (Journal of Hama University, 2024)
In a previous study, we revealed the presence of avian adenoviruses (FAdVs), which cause Inclusion Body Hepatitis, in some of broiler farms in Syria, which located in the coastal region and Homs countryside, whereas eleven out of fifteen studied samples were positive for presence of adenoviruses DNA after PCR test.The DNA concentration was measured in the PCR products of the positive samples, and we identified seven samples whose PCR products had a good DNA purity and concentration, in order to know their genetic sequence and the types to which they belong to. After subjecting them to genetic sequencing, it was found that they all belong to the avian adenovirus group E and to serotype (8b).The genetic sequences of the local isolates were compared among themselves to see how similar they were. It was found that there was a 100% match between some of the isolates, and a similarity of 98% between others, while one of the seven studied samples was different in its genetic sequence from the rest of the samples and the similarity rate ranged between 91.2% and 93.3% with the other samples.By comparing the genetic sequence of local avian adenoviruses with the genetic sequence of global isolates published in the global GenBank, it was found that the closest to the viruses diagnosed in Syria within this work is the Chinese isolate MF573922, the British isolate KT862811, and the Japanese isolate LC506173, with a percentage of 99.8%, while it was different from the Belgian isolate AF508955 and the Japanese isolate KT862810.
Keywords: Inclusion Body Hepatitis-Fowl Adenovirus - Polymerase chain reaction-Genetic Sequencing.